Phenolic extract from olive mill wastewater sustains mitochondrial bioenergetics upon oxidative insult - Iolanda Rita Infantino; Salvatore Antonio Maria Cubisino; Stefano Conti Nibali; Paola Foti; Marianna Flora Tomasello; Silvia Boninelli; Giuseppe Battiato; Andrea Magrì; Angela Messina; Flora Valeria Romeo; Cinzia Caggia; Vito De Pinto; et al. (Food Chemistry: Molecular Sciences)
In the last few years, many efforts have been devoted to the recovery and valorization of olive oil by-products because of their potentially high biological value. The olive mill wastewater (OMWW), a dark-green brown colored liquid that mainly consists of olive fruit vegetation water, is particularly exploited in this regard for its great content in phenolic compounds with strong antioxidant properties. In our previous work, we produced different OMWW fractions enriched in hydroxytyrosol- and hydroxytyrosol/oleuropein (i.e. C and OPE extracts, respectively) that exhibited considerable anti-microbial and radical-scavenging activities in vitro. Based on these findings, the present study aimed to assess the impact of C and OPE samples on mitochondrial function and oxidative stress response in mouse fibroblast-like cells (NCTC). Accordingly, OMWW phenolic extracts proved to enhance mitochondrial biogenesis and to reduce cellular sensitivity to hydrogen peroxide. Moreover, high-resolution respirometry experiments first time revealed the efficiency of OMWW phenols recovered by selective resin extraction in preventing mitochondrial respiration failure upon oxidative insult. Collected data definitely demonstrate the bioactivity of our phenolic-rich fractions, supporting the advantages of reusing the olive mill wastewater to generate, at low-cost, high added value molecules that could be useful for the improvement of health and nutrition products.